Taṭwīr Ṭarīqah Ta‘līm ‘Ilmi al-Naḥwi al-Qā’im ‘alā al-Musykilāt (Problem Based Learning) li Tarqiyah al-Taḥṣīl al-Dirāsī ladā Tilmīdhāt al-Ma‘had - Azzahro, Vivia Salma; Hamid, Abdul; Qomari, Nur (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to develop a Problem-Based Learning (PBL) model in the teaching of nahwu (Arabic grammar), to examine its feasibility through expert validation, and to analyze its effectiveness in improving the learning outcomes of female students (santriwati). This research employs a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The population of this study consisted of all second-grade KMI female students at Pondok Modern Arrisalah Ponorogo in the 2025/2026 academic year, totaling 29 students. Since the population was relatively small, a total sampling technique was employed, in which all members of the population were selected as the research sample. Therefore, the sample of this study comprised 29 second-grade KMI female students. Data were collected through observation, interviews, questionnaires, and tests (pretest–posttest), and were analyzed using the t-test and N-Gain. The results indicate that the developed PBL model is feasible, as confirmed by expert validation, in both content and instructional syntax. The implementation of the model enhances students’ engagement in learning and their ability to analyze i‘rāb. Quantitatively, the average score increased from 76.38 to 90.38, with an N-Gain of 0.601 (moderate) and a t-test significance value of 0.000 (< 0.05). In conclusion, the PBL model is effective in improving students’ learning outcomes and their analytical skills in nahwu. This model has the potential to serve as an innovative problem-solving–based approach to Arabic language learning in modern Islamic boarding schools.